2021
DOI: 10.1212/wnl.0000000000012450
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Clinical Features in Lewy Body Dementia Can Be Detected Over 6 Months

Abstract: Objective:This study aimed to quantify the trajectory and magnitude of change of the key clinical features and corresponding symptom domains of Dementia with Lewy bodies (DLB) and Parkinson’s disease dementia (PDD) including global cognition, parkinsonism, recurrent visual hallucinations, cognitive fluctuations and sleep disturbance.Methods:116 patients with Lewy body dementia (DLB=72, PDD=44) underwent assessment at baseline, 3 and 6 months as part of a prospective multi-centre randomized control trial. Linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…As expected within a neurodegenerative disease, symptomatology and disease severity progressed over time. Global cognition declined in patients with DLB, with a decline of 2.1 points on MMSE per year, similar as found in previous studies in DLB 35 , 36 and in AD. 37 When looking at individual cognitive domains, we found prominent decline on tests that address attention and processing speed.…”
Section: Discussionsupporting
confidence: 89%
“…As expected within a neurodegenerative disease, symptomatology and disease severity progressed over time. Global cognition declined in patients with DLB, with a decline of 2.1 points on MMSE per year, similar as found in previous studies in DLB 35 , 36 and in AD. 37 When looking at individual cognitive domains, we found prominent decline on tests that address attention and processing speed.…”
Section: Discussionsupporting
confidence: 89%
“…Trials focusing on prodromal or preclinical groups may choose the emergence of a clinical feature of DLB (e.g., dementia or VH) or overall function or cognition as a primary outcome. Further understanding of the progression of the different domains affected by DLB at each clinical stage of disease will be crucial to defining appropriate outcome measures [ 187 , 188 ]. A different approach will likely be needed in trials focusing on diagnosed DLB patients, where the severity of core clinical features may be a more suitable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its floor effects in patients with severe dementia, its ceiling effects in patients with mild cognitive impairment, and its lack of responsiveness to small changes noted early in PDD, limit its use as a cognitive endpoint for clinical trials in DLB [ 71 73 ]. However, it has been useful in showing the benefit of donepezil in DLB and was identified as a potential marker for change over just a 6-month interval in a recent natural history study, suggesting possible utility in future DMTs [ 43 , 74 ]. The Montreal Cognitive Assessment (MoCA) is a reliable assessment that includes items that assess attention (e.g., trail making test part B) and executive functions like working memory (e.g., digit span backward), making it a more valid instrument for DLB trials and accepted as a measure of change in regulatory trials.…”
Section: Methodsmentioning
confidence: 99%
“…RBD occurs in ≈1% of people ≥ 60, 74 but with far higher frequency in LBD. Matar et al 75 . identified 50.8% of LBD patients as having probable RBD at baseline, while Ferman et al 76 .…”
Section: Rem Sleep Behavior Disordermentioning
confidence: 99%
“…73 RBD occurs in ≈1% of people ≥ 60, 74 but with far higher frequency in LBD. Matar et al 75 identified 50.8% of LBD patients as having probable RBD at baseline, while Ferman et al 76 found that RBD was present in 76% of autopsy-confirmed DLB patients sampled. RBD has a direct association with the neurodegenerative process occurring in α-synucleinopathies, 73 such that the majority of patients with vPSGconfirmed RBD have prodromal neurodegeneration, attributable to α-synucleinopathies.…”
Section: Epidemiology and Pathophysiology Of Rbd In Lbdmentioning
confidence: 99%